2009
DOI: 10.1016/j.jfoodeng.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bread crust thickness measurement using digital imaging and L a b colour system

Abstract: a b s t r a c tA simple and new method was developed for the evaluation of baking process on bread quality through the measurement of bread crust thickness. By distinguishing the crust and crumb regions of bread, the system which uses digital imaging and the L a b colour system can predict bread crust thickness from the colour measurements of bread surface browning. Standard baking tests were conducted at different levels of temperature and time combinations to produce open breads with different crust thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(21 citation statements)
references
References 23 publications
1
19
0
1
Order By: Relevance
“…Similarly, Mohd Jusoh et al . () and Shittu et al . () found that the L *‐value of the bread crust and/or crumb decreased with increasing baking conditions.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, Mohd Jusoh et al . () and Shittu et al . () found that the L *‐value of the bread crust and/or crumb decreased with increasing baking conditions.…”
Section: Resultsmentioning
confidence: 91%
“…Mohd Jusoh et al . () observed that higher baking temperature and longer baking time produced bread with higher crust thickness that did not allow water evaporation from the crumb, leading to a very moist but also soft bread crumb.…”
Section: Resultsmentioning
confidence: 99%
“…The total color difference, ΔE of the bread slices from the reference is: Δ E = [ ( L o L ) 2 + ( a o a ) 2 + ( b o b ) 2 ] 1 2 where L o = 100, a o = 0 and b o = 0 (Mohd Jusoh et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…A thick crust developed in response to high heat accumulation in the hot zones, inducing excessive crust formation through water vaporization, protein denaturation, Maillard reaction, and caramelization at high rates. The hot zones are the zones of higher temperature increase and crust development during longer periods of any given baking time (Jefferson et al 2006;Mohd-Jusoh et al 2009).…”
Section: Resultsmentioning
confidence: 99%